Appropriations of the conceptual system of English as lingua franca in teacher education - El Kadri, Michele Salles; Rombaldi, Gabrieli (Árboles y Rizomas, 2025)
The status of English as a Lingua Franca (ELF) has generated debates in teacher education due to the challenges of incorporating it into curricula (El Kadri, 2010; Gimenez, El Kadri, & Calvo, 2018). This article aims to examine how teachers in training have appropriated the pedagogical implications of ELF in their lesson plans. We adopt English as a Lingua Franca and socio-historical-cultural theory (Vygotsky, 2001) as our theoretical framework. This qualitative study draws on the formative didactic experiment as a theoretical-methodological approach (Sforni, 2015). Data were collected from the lesson plans produced by participating students. Data analysis was conducted through the lens of ELF and the formative didactic experiment. The results indicate that participants appropriate aspects of the ELF conceptual system at varying levels, in diverse ways, and with different degrees of depth regarding specific aspects and/or implications of the concept.